Beyond the Standards: A Qualitative Analysis of Perfectionism Among Master’s-Level Counseling Students - Sara E Ellison; Jessica M Tyler; Malti Tuttle (Teaching and Supervision in Counseling, 2024)
This study investigates how perfectionism in counselor training impacts the relationships between students and clients/supervisors and contributes to imposter syndrome, burnout, and social disconnection. Using a transcendental phenomenological approach, we explored the experiences of perfectionism among 13 master’s counseling students during their graduate training. Four key themes emerged from the data analysis: (a) striving for enoughness, (b) masking inadequacy, (c) embracing vulnerability, and (d) connecting with authenticity. The implications of these findings for graduate training programs are discussed, emphasizing the specific needs of students grappling with perfectionism.
Keywords: perfectionism; counselor training; graduate students; supervision; impression management